Adaptive Interference Mitigation in GNSS - Wu, Renbiao (Navigation: Science and Technology,, 2018)
This book introduces readers to adaptive interference mitigation techniques based on multiple antennas for global navigation satellite systems (GNSS) in the time, domain, spatial and spatial-temporal domains. As the performance of GNSS can easily be impacted by various intentional and unintentional interferences, the book explores in detail various types of interference, including jamming , high dynamic jamming, spoofing, multipath and pulsed interference. It offers a valuable reference work for graduate students and engineers in the field of satellite navigation and signal processing.